Elizabethkingia meningoseptica: Case report on an emerging pathogen and its associated treatment challenges - Fabrizio Tropea; David Fraulino; Jeffrey Aeschlimann; P. Rocco LaSala; Sonia Magano (IDCases)
Elizabethkingia meningoseptica is a Gram-negative bacillus that was previously thought to rarely infect humans but recently has been identified as an emerging pathogen in both community and nosocomial settings. Typically found in the environment, this organism has been shown to infect predisposed hosts with an immunocompromised status and/or a prolonged exposure to healthcare settings. Herein, we report a case of a 78-year-old male with newly diagnosed myelodysplastic syndrome initially admitted to the hospital with pneumonia and then re-admitted after discharge with septic shock and evidence of E. meningoseptica bacteremia isolated from blood cultures. Treatment with piperacillin-tazobactam was initiated and later escalated to dual-therapy with the addition of levofloxacin. After hemodynamic stability was achieved, the patient was discharged on oral levofloxacin to complete a 21-day course of therapy. E. meningoseptica displays a unique multi-drug resistant profile that often makes initial antimicrobial selection challenging. This case illustrates the importance of early detection and use of in vitro susceptibility testing to guide therapeutic decision-making in E. meningoseptica infections; a pathogen known to have both high morbidity and mortality particularly in the immunocompromised.